The Accuracy and Acceptability of Students’ Post Editing of Idiomatic Expression Translation from English into Indonesia by Using U Dictionary - Cici Prima Yeswari; Havid Ardi (Journal of English Language Teaching, 2023)
This study aims to identify the accuracy and the acceptability of students’ post-editing of idiomatic expression translation from English into Indonesia by using U Dictionary. In this study, researchers used English students at Padang State University who had taken translation courses. Researchers use the translation test as a research instrument. This research method is descriptive qualitative. To analyze the data, the researcher identified the accuracy and acceptability of the students' post-editing results against the results of the U Dictionary. Then, the researcher calculates the average accuracy and acceptability. The researcher found that the level of accuracy and acceptability of post-editing for English students who have taken translation courses in translating idiomatic expressions is at the "almost accurate and less acceptable" level. With an average accuracy level of 2.3107. As for the level of acceptance, it is at an average of 2.3764.